Constructing Disability and Social Inequality Early in the Life Course: the case of special education in Germany and the United States - Powell, Justin (Disability Studies Quarterly, 2003)
Joining life course and educational stratification research with disability studies' complimentary emphasis on structure and disabling barriers enables a more complete analysis of the experiences and life chances of primary and secondary school students who are classified disabled. Because the processes that affect life course phases and transitions, as well as individual opportunities, identities, and attainments are cumulative, analysis of early differentiation is necessary to understand how (special) education legitimates and generates social inequality. Universal compulsory education led schools to develop a variety of sorting mechanisms. Especially during the resulting transitions within an educational system's learning opportunity structures, special educational needs are identified, labelled and categorical boundaries drawn around dis/ability altering individuals' trajectories. By stigmatizing, separating, and segregating students, special education institutions in Germany and the United States construct social inequality early in the life course.